Thread Embedding Acupuncture and Complex Korean Medicine Treatment for Lumbar Spinal Stenosis with Degenerative Scoliosis: A Clinical Case Report - Yu-Kyeong Park; Jung Hee Lee; Jae Soo Kim; Yun Kyu Lee; Hyun-Jong Lee (MEDrang Inc., 2021)
Lumbar spinal stenosis (LSS) is a common degenerative spinal condition that can have unpredictable improvement and worsening of symptoms which include low back pain, radiating pain, claudication, and degenerative lumbar scoliosis affecting quality of life. In this study, thread embedding acupuncture (TEA) was used as a conservative treatment for LSS in combination with complex Korean medicine treatments (acupuncture, herbal medicines, and physical therapy). The treatment was evaluated using the numerical rating scale, walking distance and duration, and inclination of radiological lumbar scoliosis according to antalgic posture. TEA was performed 27 times between June 8, 2020, and March 16, 2021. The patient showed improvement in numerical rating scale score from 7 to 2, pain-free walking distance from 10 m to 900 m, and scoliosis inclination following treatment. The findings of this study suggest that TEA may be helpful in the treatment of LSS.